The State of Microbiology Diagnostic of Prosthetic Joint Infection in Europe: An In-Depth Survey Among Clinical Microbiologists - Yusuf, Erlangga; Roschka, Charlotte; Esteban, Jaime; Raglio, Annibale; Tisler, Anna; Willems, Philippe; Kramer, Tobias Siegfried (Frontiers in Microbiology, 2022)
Background This study aims to give an overview on how microbiology diagnosis tests of Prosthetic joint infections (PJI) is performed in Europe, and to explore whether any factor influences the decision on implementing a test. Methods An extensive online survey of clinical microbiologists from seven European countries (Belgium, Estonia, Germany, Italy, Netherlands, Switzerland, and Spain). Following items were assessed: (i). general information on the laboratory, (ii) preference of the laboratory and clinical microbiologists regarding samples, (iii) transportation and (iv) processing of explanted foreign bodies and tissues and synovial fluid, (v) culture media and culture duration, (vi) reporting (identification and susceptibility testing), and (vii) use of molecular microbiology techniques. Results Invited were 163 clinical microbiologists. The response rate from each country was above 50% (range 51–78%), except for Germany (36%). Frequent PJI diagnostics were the use of tissue pre-processing (58.1%), culturing synovial fluid in blood culture bottles (45.5%), use of sonication for processing explanted prosthesis (56.8%), reporting the presence of synovial leukocyte counts (67%), use of blood aerobic and anaerobic agar (97.7%), and enrichment media thioglycolate (69.3%). The most common incubation time of the culture media is 7–14 days (34.1–70.5%). The clinicians were called to report the culture results (80.7%), and to give antibiotic recommendation (67%). Conclusion There are common practices in processing PJI samples and reporting results, which is promising for harmonization of PJI diagnostic in the future. However, variation in diagnostic tests should also be considered in interpreting and comparing clinical microbiology results.